Optimalisasi Reduksi Sampah di TPS 3R Tenggilis dan Super Depo Sutorejo, Kota Surabaya - Habib Dwi Putro Priambodo; Arseto Yekti Bagastyo (Jurnal Serambi Engineering, 2024)
Surabaya is a major city with a population reaching 2,88 million in 2022, with waste production rate about0,729 kg/person/day. Waste management in Surabaya involves TPS, TPS 3R, and compost houses before the waste is sent to the Benowo Landfill. The increasing waste generation rate is causing the estimated lifespan of the landfill to be insufficient in the next 10 years. To answersthis issue, efforts are needed to reduce waste to 1.000 tons/day towards the landfill, and an evaluation of the TPS3Rin Surabaya is necessary to achieve this goal. The selected study areas are TPS 3R Tenggilis and Super Depo Sutorejo as they still have 53% and 57% residual. The research is conducted by analyzing technical aspects and institutional analysis. The research results indicate the potential reduction based on scenario 1 in Tenggilis and Super Depo Sutorejo 3R TPS of 50,77% and 55,75%. Meanwhile, the potential reduction based on scenario 2 in Tenggilis 3R TPS is 60,62%, and Super Depo Sutorejo is 60,74%. In the institutional analysis, TPS 3R Tenggilis and Super Depo Sutorejo are in quadrant 1 of the SWOT quadrant position map. The applicable strategy from both 3R TPS is an expansion strategy